St. George L. Sioussat papers - Sioussat, St. George L. (St. George Leakin), 1878-1960.
Correspondence, memoranda, and notes relating chiefly to Sioussat's research on Duff Green's diplomatic career. Includes Sioussat's correspondence, 1926-1959, with American scholars and librarians concerning the location of Duff Green papers; transcripts and photostats of correspondence, 1841-1867, of Richard Cobden, Edward Everett, Duff Green, Joseph Hume, John MacGregor, Robert Peel, John Tyler, Daniel Webster, and others relating to American-British diplomacy with emphasis on Green's missions to England; and memoranda and notes from published and unpublished sources including American, British, and French newspapers, pamphlets, and diplomatic dispatches collected by Sioussat.
Historian, librarian, and archivist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cobden, Richard, -- 1804-1865 -- Correspondence; Everett, Edward, -- 1794-1865 -- Correspondence; Green, Duff, -- 1791-1875.; Green, Duff, -- 1791-1875 -- Correspondence; Hume, Joseph, -- 1777-1855 -- Correspondence; MacGregor, John, -- 1825-1892 -- Correspondence; Peel, Robert, -- 1788-1850 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Webster, Daniel, -- 1782-1852 -- Correspondence; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- 19th century; United States -- Foreign relations -- Great Britain; Archivists; Historians; Librarians